Peculiarity of Grain Boundary Diffusion of Fe and Co in Cu - Nikulkina, Valeriya; Zhevnenko, Sergei; Rodin, Alexey; Khairullin, Ainur (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2017)
In this article new experimental evidences of anomalous grain boundary diffusion (GBD) of Fe and Co in Cu were describe. To demonstrate that the brief describing of results of grain boundary diffusion in Cu with following formulation of rules which can be established on the base of the analysis of the results is presented. Experimental results which are described here concern the attempt to change the effect negative segregation by microalloying by sulfur which did not change the situation and the diffusion through foil which allowed to demonstrate the absence of accelerated GB diffusion without specific sample preparation. It is shown that GBs do not give the additional effect to the flux of Fe and Co through the foil. The extended model of surface tension gradient as an additional driving force is described.